GOALS AND TENDENCIES IN DEVELOPMENT OF THE CRYSTALLIZER BARREL TILTING MECHANISM AND THEIR COMPARATIVE CHARACTERISTICS - I. N. Golovko; D. N. Andrianov (Литьë и металлургия, 2010)
The comparative characteristics of crystallizer mechanisms with electrohydraulic and electromechanical drives are given. The main requirements to the drives used in the system of crystallizer swinging in composition of continuous casting machine are enumerated.